(3OQ GdMHH aj JGQjN MdHs - (3eMeO Hf EHQGgje Hf jhSa GdMdHj GdbGOQj GdJGPaj, QVqj GdOjf GHf GdMfHdj,J (B971 (3g` s
(3ChdgG (B:s
(3bO TGY hPGY hedC dPj GdGSeGY Ef ddJGQjN LdGdI hTQaG s
(3BNQgG (B:s
(3CHh Gdjef eMeO GdTjN Yaja GdOjf Hf Nda GdMfai JbOe PcQI ai GdeMeOjf gPG BNQ eG hLO ef gPG GdJGQjN s
(3fSNI NRGFfjI QSe GdYGde MGce OeTb YHO GdQMje GafOi GScfOQ aQGOgs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B302 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B223 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B6 - (3U (B248s
(3JHUQGJ GdCUd (B:s
Keywords: (3eJaQbGJs